Proceedings of the Seventh Italian Conference on Computational Linguistics CLiC-it 2020 Bologna, Italy, March 1-3, 2021 - Dell'Orletta, Felice; Monti, Johanna; Tamburini, Fabio (Collana dell'Associazione Italiana di Linguistica Computazionale, 2020)
On behalf of the Program Committee, a very warm welcome to the Seventh Italian Conference on Computational Linguistics (CLiC-it 2020). This edition of the conference is held in Bologna and organised by the University of Bologna. The CLiC-it conference series is an initiative of the Italian Association for Computational Linguistics (AILC) which, after six years of activity, has clearly established itself as the premier national forum for research and development in the fields of Computational Linguistics and Natural Language Processing, where leading researchers and practitioners from academia and industry meet to share their research results, experiences, and challenges.